Creative choice – about student activity and ways to expand universal competence - Sygizman, Kinga (Creativity in Business Practice. Part 2, 2019)
The chapter aims to show the possibility of developing universal competencies of students in the academic environment on the example of two radio projects: the implementation of a diploma thesis in the form of an audio reportage and the student program „Uniwersytet Łódzki na fali” presented on PR Lodz. Both initiatives are not obligatorily included in the curriculum of the „journalism and social communication” field of study. Participation in them is the result of a conscious decision of students who want to acquire new or develop their already existing journalistic skills. Based on the research conducted among the students, the author discusses their motivation to participate in projects, accompanying fears and ways to overcome them, but above all discusses many competencies that students have the chance to gain by engaging in the radio work.